A minimum income for healthy living. Issue 12 (1st December 2000) - Morris, J N; Donkin, A J M; Wonderling, D; Wilkinson, P; Dowler, E A
Abstract : BACKGROUND: Half a century of research has provided consensual evidence of major personal requisites of adult health in nutrition, physical activity and psychosocial relations. Their minimal money costs, together with those of a home and other basic necessities, indicate disposable income that is now essential for health. METHODS: In a first application we identified such representative minimal costs for healthy, single, working men aged 18–30, in the UK. Costs were derived from ad hoc survey, relevant figures in the national Family Expenditure Survey, and by pragmatic decision for the few minor items where survey data were not available. RESULTS: Minimum costs were assessed at £131.86 per week (UK April 1999 prices). Component costs, especially those of housing (which represents around 40% of this total), depend on region and on several assumptions. By varying these a range of totals from £106.47 to £163.86 per week was detailed. These figures compare, 1999, with the new UK national minimum wage, after statutory deductions, of £105.84 at 18–21 years and £121.12 at 22+ years for a 38 hour working week. Corresponding basic social security rates are £40.70–£51.40 per week. INTERPRETATION: Accumulating science means that absolute standards of living, "poverty", minimal official incomes and the like, can now be assessed by objective measurement of the personal capacity to meet the costs of major requisites of healthy living. A realistic assessment of these costs is presented as an impetus to public discussion. It is a historical role of public health as social medicine to lead in public advocacy of such a national agenda.